2020
DOI: 10.3389/fgene.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Pharmacogenetics in Primary Care: A Multi-Stakeholder Perspective

Abstract: Introduction: Aberrant pharmacogenetic variants occur in a high proportion of people and might be relevant for the prescription of over 26 drugs in primary care. Early identification of patients who metabolize these drugs more rapidly or slowly than average could predict therapeutic effectivity and safety. Yet implementation of pharmacogenetics is progressing slowly. A high public health impact can potentially be achieved by increasing the proportion of people tested, when and where eligible according to clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 36 publications
1
45
0
1
Order By: Relevance
“…Potential pathways of how GPs may encounter PGx tests are shown in Figure 2 . Recent studies have identified that barriers to PGx implementation specifically within primary care include a perceived lack of evidence for clinical utility, unclear cost effectiveness and reimbursement strategies, how to educate the primary care workforce regarding PGx, unclear roles and responsibilities particularly between general practitioners and pharmacists, the need for informatics to support PGx-informed clinical prescribing decisions, and concerns over the principles of data sharing as well as other ethical, legal and social implications (ELSI) surrounding PGx [ 190 , 191 ].…”
Section: Transitioning To the Futurementioning
confidence: 99%
“…Potential pathways of how GPs may encounter PGx tests are shown in Figure 2 . Recent studies have identified that barriers to PGx implementation specifically within primary care include a perceived lack of evidence for clinical utility, unclear cost effectiveness and reimbursement strategies, how to educate the primary care workforce regarding PGx, unclear roles and responsibilities particularly between general practitioners and pharmacists, the need for informatics to support PGx-informed clinical prescribing decisions, and concerns over the principles of data sharing as well as other ethical, legal and social implications (ELSI) surrounding PGx [ 190 , 191 ].…”
Section: Transitioning To the Futurementioning
confidence: 99%
“…In agreement with literature, our results show that current practical experience with PGx is limited, even though DPWG guidelines have been available nationwide since 2006. 2,4,7 A lack of knowledge and training amongst HCPs has previously been reported as a barrier to PGx implementation. 1,8,9,10,12,13 The community and hospital pharmacists in our study reported wanting more education about PGx for themselves and pharmacy staff.…”
Section: Practical Barriers and Facilitatorsmentioning
confidence: 99%
“…6 Nevertheless, PGx is rarely applied in current clinical practice. 2,7 A number of barriers to PGx implementation have been identified so far. These include unclear procedures, insufficient evidence, inefficient infrastructure, lack of a standardized format for reporting results, lack of ICT support tools, and lack of knowledge, training and experience among healthcare practitioners (HCPs).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenetic testing has gained popularity over the past two decades, allowing patients and providers access to information regarding potential increased or decreased efficacy of certain medications or propensity for adverse effects secondary to drug‐gene interactions 1 . Most well‐established PGx considerations have impacted specialty disciplines, such as oncology and infectious diseases, however there is increasing attention for PGx associations for medications commonly prescribed in primary care 2‐5 . Implementation of PGx in the primary care setting has lagged behind the original predictions of its widespread use 2,6 .…”
mentioning
confidence: 99%
“…Most well‐established PGx considerations have impacted specialty disciplines, such as oncology and infectious diseases, however there is increasing attention for PGx associations for medications commonly prescribed in primary care 2‐5 . Implementation of PGx in the primary care setting has lagged behind the original predictions of its widespread use 2,6 . There are several proposed barriers to widespread use of PGx testing in primary care patients.…”
mentioning
confidence: 99%